2008
DOI: 10.21273/hortsci.43.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Grape Cultivar Feeding Preference of Adult Japanese Beetles

Abstract: The Japanese beetle is a major insect pest of grapes in the eastern United States. An examination of Japanese beetle preference for currently grown grape cultivars would be useful to growers in developing pest control strategies with reduced chemical inputs. The objective of this study was to examine grape cultivar preference of Japanese beetles for commercially available grape cultivars in both cage choice and field experiments. Outdoor cage choice screening studies included 32 grape cultivars from va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Tough leaves with low nitrogen and water content likely contribute to Concord's resistance to JB defoliation, as those characteristics are indicative of poor food quality for leaf‐chewing insects 15. Others, too, have suggested that leaf physical characteristics may determine JB preference among grape cultivars 5, 6. Although not statistically significant, non‐treated Concord vines outperformed sprayed vines in a number of parameters, suggesting that adverse effects (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Tough leaves with low nitrogen and water content likely contribute to Concord's resistance to JB defoliation, as those characteristics are indicative of poor food quality for leaf‐chewing insects 15. Others, too, have suggested that leaf physical characteristics may determine JB preference among grape cultivars 5, 6. Although not statistically significant, non‐treated Concord vines outperformed sprayed vines in a number of parameters, suggesting that adverse effects (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…JBs aggregate on grapevines in response to aromatic volatile compounds released from JB‐damaged leaves 4. They tend to feed most heavily on European and French–American hybrid varieties,5, 6 but the basis for such apparent preference has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports from other authors indicate that the Japanese beetle can exhibit different feeding incidence on different plant cultivars. For instance, Gu and Pomper (2008) found that feeding incidence by the Japanese beetle on 33 cultivars of grapes varied from 42% to 49.8 ± 13.6 a n.t. Prime-Jim 47.7 ± 9.6 a n.t.…”
Section: Discussionmentioning
confidence: 99%
“…In the field, the cultivars with a low feeding incidence attracted about five times fewer Japanese beetles than those with a high feeding incidence. The results of Gu and Pomper (2008) suggest that percentage of damaged leaves reflected the attractiveness of a given grape cultivar, and that if the beetles were attracted to a particular cultivar, they fed on it, and they did not explore more feeding opportunities. In our study, feeding incidence was similar in all the blackberry cultivars investigated, in both 2017 and 2018, suggesting that all the cultivars attracted Japanese beetles with the same moderate efficacy (Tables 1 and 2).…”
mentioning
confidence: 98%
“…An evaluation of JB preference for grape cultivars was carried out by Gu and Pomper ( 2008 ) . A point system was assigned based on the % of damaged leaves per vine, as well as of leaf area loss.…”
Section: Biologymentioning
confidence: 99%